2013
DOI: 10.1007/s00382-012-1628-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Indian Ocean Dipole and Pacific recharge on following year’s El Niño: interdecadal robustness

Abstract: The Indian Ocean Dipole (IOD) can affect the El Niño-Southern Oscillation (ENSO) state of the following year, in addition to the well-known preconditioning by equatorial Pacific Warm Water Volume (WWV), as suggested by a study based on observations over the recent satellite era (1981-2009). The present paper explores the interdecadal robustness of this result over the 1872-2008 period. To this end, we develop a robust IOD index, which well exploits sparse historical observations in the tropical Indian Ocean, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 109 publications
(143 reference statements)
8
72
1
Order By: Relevance
“…Increased ENSO variance corresponds to an enhanced ENSO-IOB correlation in models (Figure 18a). A similar relationship exists for the IOD response to ENSO decadal modulations (Izumo et al 2013). For each model, the decade with the maximum correlation is compared with the decade with the minimum correlation ( Figure 18b).…”
Section: G Time-latitude Variations Along Iosupporting
confidence: 54%
“…Increased ENSO variance corresponds to an enhanced ENSO-IOB correlation in models (Figure 18a). A similar relationship exists for the IOD response to ENSO decadal modulations (Izumo et al 2013). For each model, the decade with the maximum correlation is compared with the decade with the minimum correlation ( Figure 18b).…”
Section: G Time-latitude Variations Along Iosupporting
confidence: 54%
“…Thus, the IndoPacific indices exhibit little or no relation with the NOAA/CPC modes of Northern Hemisphere atmospheric variability. On the other hand, the Indo-Pacific modes are expected to have a closer interrelation (e.g., Torrence and Webster 1999;Annamalai et al 2003;Izumo et al 2014). The values in Table 1 show that the MEI, IOD, and IMI correlate significantly with each other, and the strongest correlation is found between MEI and IMI (r 5 20.43).…”
Section: Climatic Index Characteristicsmentioning
confidence: 96%
“…The DMI-monsoon correlation is quite low in the multi observation and reanalysis mean (r = 0.27), and not even statistically significant at the 90 % level in APHRO-DITE (r = 0.10) and GPCC (r = 0.12). Thus, the IODmonsoon link appears relatively weak, as also noted by Izumo et al (2013), even though significant signatures have been identified based on composite analyses . A positive DMI is associated with an easterly wind anomaly just south of the Equator in the Indian Ocean (Fig.…”
Section: Indian Summer Monsoonmentioning
confidence: 99%
“…By contrast, Izumo et al (2013) have suggested that the bienniality of the Indo-Australian monsoon system might be a passive response to the bienniality of the IOD-ENSO system.…”
Section: Introductionmentioning
confidence: 95%